1994
DOI: 10.1213/00000539-199402000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Administration of Polymerized Gelatin Versus Isotonic Saline for Prevention of Spinal-Induced Hypotension

Abstract: This report tests the hypothesis that intravascular prehydration with 3% gelatin in electrolyte solution maintains arterial blood pressure after spinal anesthesia better than with an equal volume of isotonic saline solution. Thirty-four patients undergoing elective transurethral resection of the prostate were allocated randomly to receive either 7 mL/kg of isotonic saline 0.9% (17 patients) or 7 mL/kg of 3% gelatin in electrolyte solution (17 patients) before spinal anesthesia. There was a significant increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 0 publications
2
24
0
2
Order By: Relevance
“…This difference in the incidence is probably due to the way in which hypotension is defined and to the changes related to the pregnancy in which blood pressure is measured. The present study supports the findings of Baraka et al 22 and Dehlgen G et al 20 which demonstrated a lower incidence of hypotension in parturients undergoing elective caesarean section who were preloaded with 15 ml/kg colloid than in those who received double volume of lactated ringer solution. This small volume of colloid can be administered quickly, within 10 min, allowing rapid and effective preloading prior to spinal anaesthesia for caesarean section, which is desirable in urgent situation.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This difference in the incidence is probably due to the way in which hypotension is defined and to the changes related to the pregnancy in which blood pressure is measured. The present study supports the findings of Baraka et al 22 and Dehlgen G et al 20 which demonstrated a lower incidence of hypotension in parturients undergoing elective caesarean section who were preloaded with 15 ml/kg colloid than in those who received double volume of lactated ringer solution. This small volume of colloid can be administered quickly, within 10 min, allowing rapid and effective preloading prior to spinal anaesthesia for caesarean section, which is desirable in urgent situation.…”
Section: Resultssupporting
confidence: 92%
“…21 Baraka et al have shown that incidence of hypotension was higher in LR group than in HES group (80% vs. 40%). 22 In our study the incidence of hypotension in the Group A is in agreement with Dahlgren G et al 20 and Baraka et al 22 .…”
Section: Resultssupporting
confidence: 92%
“…9 Results showed that prophylactic administration is much more effective in attenuating hypotension following spinal anesthesia, when IM administration of either crystalloid or colloid produces equally satisfactory results. Epidural block develops slowly, which may result in moderate decrease in blood volume, which can be offered by either crystalloid or colloid.…”
Section: Discussionmentioning
confidence: 99%
“…• Preloading the patients with crystalloids or colloids like albumin, 2 Hetastarch, 15,16 Dextran, 17 and polymerized gelatin before spinal anesthesia was found to be effective in reducing the incidence of hypotension. This study was conducted on 60 patients who came for elective cesarean section under spinal anesthesia.…”
Section: Discussionmentioning
confidence: 99%